ANALISA PENGARUH FUNCTIONAL DAN CONVENIENCE RELATED FACTOR TERHADAP CONSUMER LOYALY MELALUI CONSUMER WELL BEING PADA AUTO 2000 SURABAYA - Irfan Limantoro (Jurnal Strategi Pemasaran, 2016)
Indonesian Automotive Industry Association  shows that the sales volume from January to November 2015 has reached 923 212 units. One car dealer selling car in the data products is the best-selling cars Auto 2000 Auto 2000 Surabaya included in the dealers with high sales figures and continues to rise. The condition indicates that the customer or consumer loyalty towards 2000 Auto Surabaya tend to be high. The purpose of this study was to determine and analyze the effect of functional related factors on consumer well being 2000 Auto Surabaya, determine and analyze the influence of convenience-related factors on consumer well being 2000 Auto Surabaya, as well as identify and analyze the influence of consumer well being of the consumer loyalty Auto 2000 Surabaya.